Perovskita à base de SrSnO3, caracterizada por EPR, e modificada com prata ou cobre, aplicada em fotocatálise - Silva, Adervando Sebastião da (2024)
SrSnO3 perovskite (SSO) is a material with an orthorhombic structure (Pbnm) and has been the focus of numerous studies due to its potential technological applications, such as capacitors, gas sensors, humidity sensors, among others. In recent years, the number of studies in which this material has been successfully used in other important areas, such as catalysis and photocatalysis, has been increasing. In this work, photocatalysts based on pure SrSnO3 and doped with Cu2+ were synthesized by the modified Pechini method at a calcination temperature of 900 °C for 4 h. Photodeposition of Ag on the surface of the material was also performed using UV-C radiation, Ag@SSO. The obtained powders were characterized by X-ray diffraction (XRD), infrared (IR) spectroscopy, ultraviolet-visible region, Raman spectroscopy, field emission scanning electron microscopy (FE-SEM), scanning transmission electron microscopy (STEM), electron paramagnetic resonance (EPR) spectroscopy and zeta potential. The solids were subsequently tested in the photocatalysis reaction for generation of hydroxyl radicals (•OH) through the photohydroxylation of terephthalic acid, followed by analysis by fluorescence spectroscopy. The obtained materials had the dominant phase of SrSnO3 with low or almost no presence of the secondary phase of SrCO3. The characterization of SrSnO3 by EPR revealed the presence of the novel paramagnetic species of Sn3+ in addition to three other types of defects. The results of the photocatalytic evaluation for SrSnO3 demonstrated satisfactory performance in the generation of hydroxyl radicals, unlike the Cu2+ doped system, which demonstrated considerably lower performance, which can be initially attributed to a greater recombination of charge carriers (e-/h+) after the entry of copper into the SrSnO3 Crystal lattice. The best photocatalytic performance observed was for the Agx@SSO system, possibly associated with the interaction of silver on the perovskite surface sequestering electrons and preventing the recombination of charge carriers, thus ensuring oxidationreduction reactions in the respective valence and conduction bands, favoring the generation of efficient oxidative species for photocatalytic reactions. Finally, most of the solids showed promising photocatalytic activity in tetracycline degradation, reaching approximately 77% and 74% for the Ag@SSO_0,625 and AgAF@SSO_0,625 samples, respectively. For the photohydroxylation of terephthalic acid, the solids Ag@SSO_5,0 and AgAF@SSO_2,5 demonstrated excellent photocatalytic activity in the generation of 2-hydroxy-terephthalic acid.